Pembuatan Video Animasi Materi Bangun Datar Untuk Meningkatkan Hasil Belajar: Studi Kasus pada SDN Binong Jati - Maulina, Tiara Putri; Darsiti (Melati Institute, 2023)
Binong Jati Public Elementary School, which is located at Jalan Binong, is an elementary school engaged in education and eductive. In the world of education, there are still many obstacles when facing the learning process, one of which is learning flat shape material which some students may find difficult to understand. Flat shapes are one of the important materials in the elementary school curriculum. However, some students have difficulty understanding these flat shapes due to several obstacles, such as the lack of facilities and infrastructure in schools. For this reason, the author tries to help design animated video media for learning flat shapes to facilitate and improve student learning outcomes using Adobe Premiere Pro. At the analysis stage, identification of student learning needs at SDN Binong Jati is carried out as well as data collection regarding the difficulties students often face in understanding geometric material. flat. Furthermore, the design of instructional media in the form of animated videos was designed based on the principles of effective learning and the characteristics of students at the school. At the development stage, animated videos were created using the Adobe Premiere Pro application. This application allows for professional creation with complete features and flexible editing capabilities. This animated video is arranged in a systematic and structured manner, following the correct sequence of concepts and learning stages. The use of animation in the video aims to clarify concepts and visualize the use of flat shapes in everyday contexts. Furthermore, the animated videos that have been made are implemented in the learning process at SDN Binong Jati. Students are given access to watch animated videos independently or as part of classroom learning. After that, an evaluation was carried out on the effectiveness of using animated videos in improving student learning outcomes. The evaluation is carried out through an understanding test. The results of this study are expected to provide benefits in the development of innovative and interesting learning media using the Adobe Premiere Pro application to improve student learning outcomes in flat shape material at SDN Binong Jati.